2022
DOI: 10.1136/bmjopen-2021-056239
|View full text |Cite
|
Sign up to set email alerts
|

Improving primary prevention of acute rheumatic fever in Australia: consensus primary care priorities identified through an eDelphi process

Abstract: ObjectivesTo establish the priorities of primary care providers to improve assessment and treatment of skin sores and sore throats among Aboriginal and Torres Strait Islander people at risk of acute rheumatic fever (ARF) and rheumatic heart disease (RHD).DesignModified eDelphi survey, informed by an expert focus group and literature review.SettingPrimary care services in any one of the five Australian states or territories with a high burden of ARF.ParticipantsPeople working in any primary care role within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Similarly, a recent eDelphi study about prevention of ARF revealed that primary care staff wanted greater focus on environmental health and housing, employment of Aboriginal and Torres Strait Islander health professionals and genuine community engagement, but they felt they had limited opportunity to influence these factors from primary care roles. 8 Many of these themes mirror the perspectives of hospital-based healthcare workers in tertiary Aboriginal health services in northern Australia, who have expressed dismay at systems barriers to culturally safe care. 9,10 In the wake of the Four Corners program, this article offers a constructive foundation for reflection by primary care staff and identifies some of the ways that individual practitioners may be able to contribute to better health and healthcare experiences for Aboriginal and Torres Strait Islander people.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, a recent eDelphi study about prevention of ARF revealed that primary care staff wanted greater focus on environmental health and housing, employment of Aboriginal and Torres Strait Islander health professionals and genuine community engagement, but they felt they had limited opportunity to influence these factors from primary care roles. 8 Many of these themes mirror the perspectives of hospital-based healthcare workers in tertiary Aboriginal health services in northern Australia, who have expressed dismay at systems barriers to culturally safe care. 9,10 In the wake of the Four Corners program, this article offers a constructive foundation for reflection by primary care staff and identifies some of the ways that individual practitioners may be able to contribute to better health and healthcare experiences for Aboriginal and Torres Strait Islander people.…”
Section: Discussionmentioning
confidence: 97%
“…Wyber et al. (2022) emphasised the importance of culturally responsive care in RF prevention for indigenous populations, as it encourages engagement and participation in services. However, the Westernised medical model of healthcare in Aotearoa, NZ does not align with Māori and Pacific holistic approaches to health (Office of the Prime Minister’s Chief Science Advisor, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This situation could be associated with the following facts. First, there is no uniform consensus in Australasia on how to improve the primary prevention of RHD (40). Second, there are disparities in diverse practices among various indigenous populations, restricting their access to healthcare, housing, and education (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%